The Relationship of Online Brand Community, Value Creation Practices, Brand Trust, and Brand Loyalty - Dien Mardhiyah; Ali Imaduddin Futuwwah; Mohd Faiz Hilmi; Dinda Oktaviona Rosidi; Nur Habiba Zain (Universitas Airlangga, 2023)
Objective: Companies are realizing the potential of the online brand community to increase consumer relationships. Online Brand community keeps customers using the company's products through all community activities. This study investigates the effect of the activity in the online brand community on value co-creation practices to create brand trust and brand loyalty. Design/Methods/Approach: An online survey was conducted by distributing a questionnaire among 319 members of an online brand community. The collected data was analyzed using Structural Equation Modeling (PLS-SEM). Findings: Online brand communities influence value co-creation practices (social networking, community engagement, impression management, and brand use). In this study, social networking and impression management influence brand trust and brand loyalty. However, community engagement and brand use do not affect brand trust. The role of brand trust affects the creation of brand loyalty in online brand community members. Originality/Value: This study examines the effect of value co-creation practices in online brand communities on brand trust and brand loyalty in brand communities found in one country with a high collectivity level. Not all community value co-creation activities have the effect of creating brand trust due to conditions within the community. Practical/Policy implication: The practical implication is to guide marketers to pay attention to some value co-creation activities in online brand communities that can create brand trust in brand communities with a high culture of collectivity. Companies understand the dynamics of online brand communities and relevant strategies in high collectivity cultures, as well as leveraging the potential of social networks while overcoming the challenges posed by the abundance of information on the internet.